Review Of Marital Rape In Law No. 23 Of 2004 Concerning The Elimination Of Household Violence (TPKDRT), And Law No. 12 Year 2022 Concerning Criminal Acts Of Sexual Violence (TPKS) Feminism Perspective - Ulfa Fitriyah; Busriyanti Busriyanti; Sri Lumatus Sa'adah (Syntax Corporation Indonesia, 2023)
Violations regarding sexual harassment need to be known so far; according to the public perspective, it is generally interpreted as adultery, samen leven (cohabitation), homosexuality, obscenity, prostitution, and acts of violence committed by a man against a woman, both of whom are not married. Such is the scope of sexual harassment that has been understood so far. Often there is no term regarding rape committed by a husband against his wife, or what we are currently familiar with is marital rape. Even marital rape is considered an oxymoron. However, even though it is still ambiguous, the facts that emerge based on reports in various complaint institutions indicate a high prevalence related to marital rape. Therefore this study aims to answer the research problem, Marital Rape in Law No. 23 of 2004 concerning the Elimination of Domestic Violence , and Law No. 12 of 2022 concerning Crimes of Sexual Violence ? and How to study the criminal sanctions of Marital Rape in Law no. 23 of 2004 concerning the Elimination of Domestic Violence , and Law no. 12 of 2022 concerning Crimes of Sexual Violence from a Feminism Perspective? This research uses a type of normative legal research using the method of literature and statutory approaches. Data collection techniques using data analysis were carried out using inductive descriptive techniques, the validity of which was content analysis. The results of this research show the elements of marital rape in the Law of concerning the Elimination of Domestic Violence , the Crimes of Sexual Violence, sanctions, and how these laws respond to marital rape behavior, and philosophically based on feminist legal theory, the legislation represents the feminist movement itself.